2022
DOI: 10.1183/13993003.01506-2022
|View full text |Cite
|
Sign up to set email alerts
|

RIPK1 kinase-dependent inflammation and cell death contribute to the pathogenesis of COPD

Abstract: RationaleReceptor-interacting protein kinase 1 (RIPK1) is a key mediator of regulated cell death (including apoptosis and necroptosis) and inflammation, both drivers of chronic obstructive pulmonary disease (COPD) pathogenesis.ObjectiveWe aimed to define the contribution of RIPK1 kinase-dependent cell death and inflammation in the pathogenesis of COPD.MethodsWe assessedRIPK1expression in single-cell RNA-sequencing data from human and mouse lungs and validated RIPK1 levels in lung tissue of COPD patientsviaimmu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…In addition, oxidative stress in the lungs regulates nuclear histone modification such as methylation, acetylation, and phosphorylation that is suggested to cause chromatin remodeling, recruitment of basal transcription factors, and RNA polymerase II, leading to increased pro-inflammatory responses [ 40 , 41 , 42 ]. Studies have reported that CS-induced mtROS in COPD patients contributes to an alteration in mitochondrial fission and fusion proteins [ 44 , 45 , 46 ], increased oxidative stress gene signatures [ 47 ], lower mitochondrial membrane potential and ATP levels [ 48 ], impaired mitophagy and concomitant aggregation of damaged and dysfunctional mitochondria [ 35 , 49 , 50 ], and necrosis [ 51 , 52 , 53 ]. In line with this, immune cells in COPD exhibit altered metabolic function, including glycolysis and fatty acid oxidation [ 54 , 55 , 56 , 57 , 58 ], which are important processes required for ATP production to fuel energy demanding immune functions [ 59 ].…”
Section: Oxidative Stress In Copdmentioning
confidence: 99%
“…In addition, oxidative stress in the lungs regulates nuclear histone modification such as methylation, acetylation, and phosphorylation that is suggested to cause chromatin remodeling, recruitment of basal transcription factors, and RNA polymerase II, leading to increased pro-inflammatory responses [ 40 , 41 , 42 ]. Studies have reported that CS-induced mtROS in COPD patients contributes to an alteration in mitochondrial fission and fusion proteins [ 44 , 45 , 46 ], increased oxidative stress gene signatures [ 47 ], lower mitochondrial membrane potential and ATP levels [ 48 ], impaired mitophagy and concomitant aggregation of damaged and dysfunctional mitochondria [ 35 , 49 , 50 ], and necrosis [ 51 , 52 , 53 ]. In line with this, immune cells in COPD exhibit altered metabolic function, including glycolysis and fatty acid oxidation [ 54 , 55 , 56 , 57 , 58 ], which are important processes required for ATP production to fuel energy demanding immune functions [ 59 ].…”
Section: Oxidative Stress In Copdmentioning
confidence: 99%
“…Cigarette smoking exposure remains a dominating risk factor for developing COPD, which contributes to the imbalance in inflammatory response, and necroptosis of epithelial cells in the lungs 43 . Among the core necroptotic regulators, RIPK1 protein is notably overexpressed in the airway epithelium of COPD patients versus never‐smokers and smokers without airflow limitation 44 . Meanwhile, phosphorylated MLKL is notably induced in the advanced stages of cigarette smoke‐mediated emphysema in pulmonary epithelial cells while apoptotic signals can be maximally induced in the early stages of cigarette smoking exposure 45 .…”
Section: The Key Molecular Mechanisms Underlying Necroptosis Of Speci...mentioning
confidence: 99%
“…43 Among the core necroptotic regulators, RIPK1 protein is notably overexpressed in the airway epithelium of COPD patients versus neversmokers and smokers without airflow limitation. 44 MUC1 (mucin 1) is a membrane-tethered mucin glycoprotein, which is primarily expressed on the surface of airway epithelial cells. 46 In addition to anti-inflammation and anti-apoptosis against infection, 47,48 MUC1 expression is elevated in airway epithelial cells in response to TNF-α, and interacts with RIPK1 but not with RIPK3.…”
Section: Inflammationmentioning
confidence: 99%
“…7 Inflammation and cell death are two distinct but highly interconnected and mutually regulated phenomena that are important in immune defense, pathogenesis, and maintaining organismal homeostasis. 8,9 Both inflammation and cell death are also recognized as host-mediated mechanisms that facilitate the elimination of invading pathogens. 10 Despite progress in understanding periodontitis, many challenges remain in uncovering the molecular mechanisms behind its pathogenic processes, necessitating further research.…”
Section: Introductionmentioning
confidence: 99%
“…Microbial infection and host immune‐inflammatory responses are the key factors affecting the pathogenesis of periodontitis 7 . Inflammation and cell death are two distinct but highly interconnected and mutually regulated phenomena that are important in immune defense, pathogenesis, and maintaining organismal homeostasis 8,9 . Both inflammation and cell death are also recognized as host‐mediated mechanisms that facilitate the elimination of invading pathogens 10 .…”
Section: Introductionmentioning
confidence: 99%